2012
DOI: 10.1080/19317611.2012.691443
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Motivations of Vaginal Practices in Tete Province, Mozambique

Abstract: Vaginal practices have been linked with an increase in risk for HIV transmission and other harms. In 2007, a household survey of 919 women was conducted in Tete province,Mozambique, as part of the World Health Organization Multicountry Study on Gender, Sexuality, and Vaginal Practices. Women aged 18 to 60 years old were interviewed to determine prevalence and motivations for vaginal practices. A large range of frequently used practices was identified. Nearly 80% of women reported three or more current practice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Labia minora elongation is typically initiated during adolescence, before sexual debut, but needs to be maintained throughout adulthood (Martin Hilber, Hull et al 2009, Hull, Hilber et al 2011, François, Bagnol et al 2012, Martin Hilber, Kenter et al 2012). Thus by adulthood, the majority of women will have completed this initial process; women in Zambézia are no exception.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Labia minora elongation is typically initiated during adolescence, before sexual debut, but needs to be maintained throughout adulthood (Martin Hilber, Hull et al 2009, Hull, Hilber et al 2011, François, Bagnol et al 2012, Martin Hilber, Kenter et al 2012). Thus by adulthood, the majority of women will have completed this initial process; women in Zambézia are no exception.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, labia minora elongation is typically practiced among girls at puberty initiation, under the supervision of older family members and generally completed before sexual initiation (François, Bagnol et al 2012, Martínez Pérez, Mubanga et al 2015). Labia minora elongation has commonly been practiced in central and northern Mozambique, but has experienced a recent resurgence of popularity in southern provinces(Arnfred 2011).…”
Section: Introductionmentioning
confidence: 99%
“…However, this finding is inconsistent with other qualitative studies in which pain has been widely identified as a common adverse effect of LME (Grassivaro Gallo & Villa, 2006;Martínez Pérez & Namulondo, 2011;Martínez Pérez, Tomáz Aznar & Bagnol, 2013). No other symptoms, such as irritation, itching, swelling, and dyspaurenia, which are, together with pain, the most common adverse effects of LME reported by participants of the household survey in Tete, Mozambique (Hull et al, 2011;François, Bagnol, Chersich, Mbofana, Mariano, Nzwalo et al, 2012), were mentioned by either the male respondents or the female key informants of this study.…”
Section: Discussionmentioning
confidence: 99%
“…The present research thus represents the first account of this type. This paper draws on quantitative data collected in a World Health Organization (WHO)led Gender, Sexuality and Vaginal Practices (GSVP) multi-country prevalence study conducted in 2007 in Tete Province (central Mozambique) 14,15,16,17,18,19,20 . Although the data were collected nearly ten years ago, we believe that they can still provide useful insights to improve the understanding of the health implications of this widespread genital modification practice.…”
Section: And Inmentioning
confidence: 99%
“…Data from the GSVP survey reporting the prevalence, motivations and timing of LME has previously been published 14,15 . Those findings showed that LME was universal in the area 14,15 .…”
Section: And Inmentioning
confidence: 99%